Correction: The impact of sarcopenia on clinical outcomes in men with metastatic castrate-resistant prostate cancer. - Efthymios Papadopoulos; Andy Kin On Wong; Sharon Hiu Ching Law; Lindsey Ze Jing Zhang; Henriette Breunis; Urban Emmenegger; Shabbir M H Alibhai (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0286381.].